2022
DOI: 10.13057/biodiv/d230206
|View full text |Cite
|
Sign up to set email alerts
|

Mangrove species diversity and carbon stock in silvofishery ponds in Deli Serdang District, North Sumatra, Indonesia

Abstract: Abstract. Harefa MS, Nasution Z, Mulya MB, Maksum A. 2021. Mangrove species diversity and carbon stock in silvofishery ponds in Deli Serdang District, North Sumatra, Indonesia. Biodiversitas 23: 655-662. Mangrove-based silvofishery ponds are promoted as a win-win solution for biodiversity conservation, climate change mitigation as well as income generation for coastal communities. This study aimed to analyze the species diversity and carbon stock of mangrove vegetation in silvofishery ponds in Tanjung Rejo Vil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 35 publications
0
26
2
2
Order By: Relevance
“…However, species composition in Benoa Bay's Rhizophora zone had a higher species number than Mare Island (Akbar et al 2016), Jakarta Bay , Situbondo, East Java (Hariyanto et al 2019), Mantehage-Paniki Islands, North Sulawesi (Opa et al 2019) and Cirebon (Purwanto et al 2022) were only found five true mangrove species. Several mangrove species were co-dominantly identified with Rhizophora, such as A. alba, B. hainesii, B. parviflora, E. agallocha, H. littoralis, L. littorea, S. hydrophyllacea, S. ovata and X. moluccensis, as found in Riau (Prianto et al 2006), and A. officinalis, B. cylindrica, B. sexangula, S. caseolaris in North Sumatra, Indonesia (Harefa et al 2022). The importance value index of the Rhizophora genus in this zone was 217.23%, while the cumulative IVI of other species was only 82.77% (Figure 4).…”
Section: Mangrove Community Structurementioning
confidence: 90%
“…However, species composition in Benoa Bay's Rhizophora zone had a higher species number than Mare Island (Akbar et al 2016), Jakarta Bay , Situbondo, East Java (Hariyanto et al 2019), Mantehage-Paniki Islands, North Sulawesi (Opa et al 2019) and Cirebon (Purwanto et al 2022) were only found five true mangrove species. Several mangrove species were co-dominantly identified with Rhizophora, such as A. alba, B. hainesii, B. parviflora, E. agallocha, H. littoralis, L. littorea, S. hydrophyllacea, S. ovata and X. moluccensis, as found in Riau (Prianto et al 2006), and A. officinalis, B. cylindrica, B. sexangula, S. caseolaris in North Sumatra, Indonesia (Harefa et al 2022). The importance value index of the Rhizophora genus in this zone was 217.23%, while the cumulative IVI of other species was only 82.77% (Figure 4).…”
Section: Mangrove Community Structurementioning
confidence: 90%
“…The estimated carbon stock from AGB in this study was relatively higher compared to other locations in Indonesia, for example in Lamongan East Java (53.89 ton C ha -1 ), Tanakeke South Sulawesi (37.6 ton C ha -1 ) and Deli Serdang North Sumatra (40-50 ton C ha -1 ) (Asadi et al 2017;Cameron et al 2019;Harefa et al 2022). The abovementioned locations have similarities in the growth of rehabilitated mangrove areas at a relatively young age (<30 years).…”
Section: Carbon Stock and Co2 Sequestration Estimationmentioning
confidence: 62%
“…The physical condition of mangrove vegetation can reveal the density of the ecosystem. This condition requires an environmental form that can be identified using various parameter values such as stem diameter, height, dominance, relative dominance, frequency, and relative frequency [10]. Vegetation data were analyzed to measure the relative values of density, frequency, abundance, and species dominance.…”
Section: Discussionmentioning
confidence: 99%